Considerations Regarding the Possibility of Emphasising the Virtual Currency Transactions in Accounting - Riana Iren RADU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2017)
The phenomenon of virtual currency, and especially the virtual currency Bitcoin, have managed to draw attention of the population, organizations and governments, from the moment of its appearance, proliferating pro and against attitudes against their use in the day-to-day transactions. The study is a detailed analysis of the virtual currency phenomenon and an attempt to outline a possible status from the accounting point of view of the virtual worlds, starting from the position adopted by the regulating authorities in the countries where the virtual currencies register the highest rate of use.